Natural History of Intracranial Atherosclerotic Disease - Pu, Yuehua; Dou, Xin; Liu, Liping (Frontiers in Neurology, 2014)
Intracranial atherosclerotic disease was very common among stroke patients of Asians, Blacks, and Hispanics ancestry. Furthermore, stroke patients with intracranial atherosclerosis (ICAS) have higher recurrence rate of cerebral ischemia and death than those without ICAS. However, the natural history of intracranial atherosclerotic disease is still in controversy. Most of the studies were retrospective and randomized controlled trial of drugs. This review summarized the prognosis of symptomatic and asymptomatic intracranial atherosclerotic disease in order to guide clinical decision-making and further clinical research.